Mangrove distribution and diversity during three Cenozoic thermal maxima in the Northern Hemisphere (pollen records from the Arctic–North Atlantic–Mediterranean regions). (17th September 2021) - Popescu, Speranta‐Maria; Suc, Jean‐Pierre; Fauquette, Séverine; Bessedik, Mostefa; Jiménez‐Moreno, Gonzalo; Robin, Cécile; Labrousse, Loïc
Abstract: Aim: Past pollen records reveal the changes in latitudinal distribution of plants in relation to climate, particularly their expansion in response to global warming. The maximum northward expansion of the mangrove genus Avicennia since the Early Eocene is known, but this information is missing for other mangrove taxa. Here, we evaluate the diversity of past mangroves with respect to latitude during three Cenozoic thermal maxima (PETM: 56 Ma; EECO: 54–49 Ma; MMCO: 17–14 Ma). Location: North Atlantic, Mediterranean. Taxa: Avicennia, other mangrove taxa (Rhizophoraceae, Nypa, Xylocarpus, Pelliciera, etc.). Method: We collected well‐dated marine sediments along a Northern Hemisphere latitudinal transect and we analysed their pollen content in order to compare the past distribution of mangrove taxa with the present. The analysis of 89 samples (PETM: 13; EECO: 31; MMCO: 45) was performed and interpreted using a robust botanical background for identification of pollen grains and their representativeness in marine sediments. Results: During the Early Eocene, two palaeolatitudinal thresholds at 65–70°N and 35°N, respectively, delimited the Avicennia ‐only mangrove from a diversified but scrawny mangrove and finally from a diversified and well‐developed mangrove. The Avicennia threshold was selective at 40°N during the Mid‐Miocene. The Avicennia range limit was up to 10–15° poleward of the limit for other mangrove taxa during the Early Eocene and the Mid‐Miocene compared with 9° at present. Main conclusions: A buffer zone characterised by a diversified but scrawny mangrove co‐occurring with a few megathermal plants occurred in the Early Eocene between 35°N and 65–70°N. This finding questions the relative influence of a more 'equable' climate and/or the ability of some taxa to expand towards areas with cooler conditions in the past. Mangrove provincialism, which was established progressively after the Early Eocene, was probably forced by plate tectonics. The taxonomic impoverishment of the Atlantic East Pacific province was probably caused by successive periods of global cooling. These results support the Tethyan origin of the mangroves.